Stigma reduction initiatives: caregivers of multi faces - Zamri Hassan (Routledge, 2016)
Issues related to HIV/AIDS often revolve around stigma and discrimination, which have led the caregivers of people living with HIV/AIDs (PLWHAs) to develop initiatives for reducing stigma and discrimination. The objective of this research was to identify these stigma reduction initiatives devised to lessen the stigma and discrimination. A total of 27 research participants were interviewed. Findings revealed that the caregivers of PLWHAs developed new identities which their society consider good and acceptable. Preventing disclosure was able to reduce the stigma and discrimination. This research yields important insights on the urgent need to initiate stigma reduction strategies to ensure inclusion.